New Material of Carbonaceous Compressions from the ∼1.5 Ga Singhora Group, Chhattisgarh Supergroup, India, and their Interpretation as Benthic Algae - Singh, Veeru Kant; Sharma, Mukund (Frontiers in Earth Science, 2022)
The origin, antiquity, and affinity of benthic seaweeds (multicellular algae) in the geological past are shrouded in mystery due to their preservation bias. In this study, we present a new material of well-preserved carbonaceous compression fossils in shale horizons of the Mesoproterozoic (ca. ∼1,500–1,300 Ma) Singhora Group of the Chhattisgarh Supergroup. Eleven distinct taxa, including one new taxon, Palaeoscytosiphon shuklaii, n. gen. et. sp., and one new species, Jiuqunaoella sergeevii, n. sp., are established. Four unidentified morphologies are also reported. Morphologically, the carbonaceous fossils are fan-shaped, palmate, elongated, leaf-like algal thalli with/without holdfast at the base, isolated or dichotomously branched long filaments, along with multicellular reproductive structures. The results of laser Raman spectroscopy and energy dispersive X-ray spectroscopy (EDX) are also presented in support of their biogenicity. Collectively, the preservation mode of the Singhora carbonaceous fossils suggests multicellular algal affinity and adds to a Burgess Shale-type (BST) taphonomic window in the Pre-Ediacaran biosphere.